Fake News on Social Media and Adolescent’s Cognition - Suraya Mansur; Nurhayani Saragih; Rajab Ritonga; Novita Damayanti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
This research aims to determine the extent to which teenagers distinguish true news from fake news and how these fake news affect adolescents’cognition. A lot of hoax information has sprung up on social media, especially during the 2019 Indonesian presidential election. The ability to check on the information spread in online media is influenced by each individual’s cognitive abilities. A person’s cognitive ability is to think rationally, including aspects of knowledge, understanding, application, analysis, synthesis, and evaluation. This study used an explanative survey method with a quantitative positivistic paradigm. The results showed that the most influencing X variable to the Y variable was the Satire variable, which is positive and unidirectional. The Hoax variable has the most influence on cognitive abilities, even though the value is negative and not unidirectional. This means, the lower the understanding of Hoax, the higher the level of cognitive abilities.